Peranan Keluarga Sebagai Faktor Protektif Bagi Kesejahteraan Psikologi Mental Remaja - Fitri Inayah; Moh. Jalaluddin; Faridatul Jannah; Desi Endang Maisuri (Yayasan Cendekia Gagayunan Indonesia, 2025)
Adolescents constitute an age group particularly vulnerable to psychological stress due to biological changes, social transitions, and academic demands. This study aims to analyze the role of the family as a protective factor in maintaining and enhancing adolescents’ psychological well-being. Employing a qualitative approach based on literature review, data were obtained from classical literature, books, and scholarly journals. The findings indicate that the forms of family support with the greatest influence include emotional support, open communication, and familial warmth. These results reinforce the theory that the family functions as a protective factor capable of mitigating the negative impact of stress and social pressure on adolescents. The study further recommends the importance of family empowerment programs to enhance the active role of parents in supporting adolescent mental health. Accordingly, strengthening family functions emerges as a strategic step toward fostering a younger generation that is more psychologically healthy and happy.